THE EFFECT OF COMBINATION OVATIDEWITHhCG ON OVULATION AND HATCHING OF FISH EGGOF PAWAS (Osteochilus hasselti C.V) - Desy Kristina Ayu Sirait; Netti Aryani; Nuraini Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The aim of this research was to determine the effect of combination Ovatide with hCG on ovulation and hatching of fish egg of Pawas (Osteochilus hasselti C.V). This research was conducted from May-October 2018 at Fish Hatchery and Breeding Laboratory, Fisheries and Marine Science Faculty Riau University. The method used is an experimental method with a Completely RandomizedDesign (CRD)with five treatments and three replications.The treatment were P1 (Ovatide 0,5 ml/kg + 0 IU/kg body weight hCG), P2 (Ovatide 0,5 ml/kg + 450 IU/kg body weight hCG), P3 (Ovatide 0,5 ml/kg + 550 IU/kg body weight hCG), P4 (Ovatide 0,5 ml/kg + 650 IU/kg body weight hCG), P5 (Ovatide 0 ml/kg + 550 IU/kg body weight hCG). The result showed thatcombination Ovatide with hCG on P3 (Ovatide 0,5 ml/kg + 550 IU/kg body weight hCG)was the highest of P3 with latency period 5,06 hours, number off egg stripping 179 egg/g broodstock, ovisomatic index 16,43%, increase of diameter egg 0,104 mm, increase of egg maturation 14%, fertilization rate 91,26%, hatching rate 90,17%, and survival rate 90,38%. The water quality parameters during research was in optimal range temperature 25-28°C, pH 6and dissolved oxygen 3,77-5,20 mg/l. Keywords :Osteochilus hasselti C.V, Ovatide, hCG, Ovulation, and Hatching rate